Anthem - Rand, Ayn, 1905-1982 (Salt Lake City, UT : Project Gutenberg, 1998)
"Anthem" by Ayn Rand is a dystopian novella written in 1937 and first published in 1938. In a future Dark Age where individuality has been erased and technology is controlled, a young man named Equality 7-2521 commits a forbidden act: secret scientific research. When his transgression is discovered, he flees into the wilderness with Liberty 5-3000, the woman he loves. Together, they seek to rediscover what their society has destroyed$1 (Bthe concept of the individual self. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Anthem_(novella)
There is a different edition at #1250. The file anthm10z.* is a comparison of both.
Release date is 1998-03-01
This Etext was prepared by an anonymous group of volunteers
Keywords: Science fiction; Psychological fiction; Love stories; Time travel -- Fiction; Men -- Psychology -- Fiction; Individuality -- Fiction